Let's go rock collecting - Gans, Roma, 1894-; Keller, Holly (New York : HarperCollins, 1997)
Describes the formation and characteristics of igneous, metamorphic, and sedimentary rocks and how to recognize and collect them.
Keywords: Rocks -- Collection and preservation -- Juvenile literature; Rocks -- Collection and preservation